FACTORS INFLUENCING FARMERS’ DECISIONS TO PURCHASE CERTIFIED RICE SEEDS OF UD RESTU TANI JEMBER - Dina Epriliyanti; Joni Murti Mulyo Aji (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2021)
The use of certified rice seeds has several weaknesses, including the price of grain that is rela- tively the same as non-certified rice seeds and production that is not optimal if the varieties of seeds planted are not replaced every planting season. Therefore, the seed industry is trying to improve the ser- vice quality and products, as was done by UD. Restu Tani, which is by segmenting the quality of seeds. This study aims to determine the factors that influence farmers’ decisions to purchase certified rice seeds UD Restu Tani and to analyze the attributes that influence farmers’ decisions to purchase certified rice seeds. The research was conducted in Jember Regency. The sampling method was carried out using convenience sampling with 126 samples. The results showed that (1) the factors that influenced the farmers’decision to purchase certified rice seeds of UD Restu Tani with a real level of 10% were educa- tion, age, and quality of the seeds and (2) the farmers’ decision to purchase certified rice seeds was in - fluenced by five new factors, including planting technical information, product certification validity fac- tor, seed product availability factor, seed product quality, and seed product price.